2017
DOI: 10.1177/0031512517700054
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multichannel Near Infrared Spectroscopy to Study Relationships Between Brain Regions and Neurocognitive Tasks of Selective/Divided Attention and 2-Back Working Memory

Abstract: While dichotic listening (DL) was originally intended to measure bottom-up selective attention, it has also become a tool for measuring top-down selective attention. This study investigated the brain regions related to top-down selective and divided attention DL tasks and a 2-back task using alphanumeric and Japanese numeric sounds. Thirty-six healthy participants underwent near-infrared spectroscopy scanning while performing a top-down selective attentional DL task, a top-down divided attentional DL task, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…The present study aimed to use the DL task to examine relationships between self-reported social anxiety and brain activity, based on top-down attentional control functioning (Tomita et al., 2017). We also investigated the relationship between social situation-dependent internal/external attention biases (self-reported self-focused attention and external attention bias) and social situation-independent attentional control functions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study aimed to use the DL task to examine relationships between self-reported social anxiety and brain activity, based on top-down attentional control functioning (Tomita et al., 2017). We also investigated the relationship between social situation-dependent internal/external attention biases (self-reported self-focused attention and external attention bias) and social situation-independent attentional control functions.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were Japanese, and no participants had any diagnosed psychological disorders including SAD, hearing problems, neurological or cardiovascular illnesses, poor physical conditions, lack of sleep, and medication use within 24 hours; and none had drunk alcohol within 12 hours of beginning of the experiment. The participants were the same as those in a previously published study by Tomita et al (2017). This study received ethical approval from the university's ethics committee.…”
Section: Methods Participantsmentioning
confidence: 99%
See 3 more Smart Citations